Immunostimulant Application of Chlorella Vulgaris on the Growth of Vaname Shrimp (Litopenaeus vannamei) in Gresik - Gunanti Mahasri; Daruti Dinda Nindarwi; Hapsari Kenconojati; Daud Dharmansyah; Adelia Inas Shafira; Afifah Elok Firdaus; Faisol Mas’ud; Endah Sih Prihatini; Fuquh Rahmat Shaleh (Universitas Islam Lamongan, 2026)
This activity aims to improve the defense of harvests and the bodies of vaname shrimp (Litopenaeus vannamei) in ponds in Gresik Regency through the application of immunostimulants from Chlorella vulgaris. The main problems faced by farmers include high shrimp mortality rates due to declining water quality and pathogen infections. The use of antibiotics has proven to be ineffective and causes residues in aquaculture products, which are harmful to health. Therefore, an environmentally friendly biotechnology approach through the use of natural immunostimulants is a more sustainable alternative. The implementation method included collaboration between the community service team, the Fisheries Service, and farmer groups in Mojoasem and Pangkah Wetan villages, Ujung Pangkah subdistrict, Gresik Regency. The stages of the activity consisted of socialization, training in the production and application of Chlorella vulgaris based immunostimulants, and assistance in applying the technology in ponds. The results of the activity showed that the use of Chlorella vulgaris immunostimulants had a significant effect on the growth and survival parameters of vaname shrimp.0020The 28-day maintenance period yielded the best results in terms of survival rate (SR) of 100%, specific growth rate (SGR) of 4.17%, and absolute weight and length growth of 1.39 grams and 1.10 cm. The application of immunostimulants can enhance immune response, maintain water quality stability, and reduce shrimp mortality rates. Thus, this technology has the potential to become an innovative strategy in the development of shrimp farming in the coastal areas of Gresik.